An Alternative Method for the Study of Impulsive Differential Equations of Fractional Orders in a Banach Space. (12th August 2013) - Bouzaroura, Asma; Mazouzi, Saïd
Abstract : This paper is concerned with the existence, uniqueness, and stability of the solution of some impulsive fractional problem in a Banach space subjected to a nonlocal condition. Meanwhile, we give a new concept of a solution to impulsive fractional equations of multiorders. The derived results are based on Banach's contraction theorem as well as Schaefer's fixed point theorem.